Integration Between Aqli And Naqli In Development Of Database For Hospital Information System - Muhammad Mursyidan Mah Dahwi; Asma Abd Rahman; Azlan Husin; Rosline Hassan; Waidah Ismail (International Journal of Scientific & Technology Research, 2024)
Database era has been appear during Prophet Muhammad S.A.W. We are using the same concept but only deployed in the medical environment with security features which is related to aqli and naqli. The development of a system not only covered the ability of the system to be functioned and execute very well but a good and efficient system must be able to communicate with the users and become a user friendly system. This research is about developing Hospital Patient Information System developed for Hematology Ward and Hemato-oncology Laboratory at the Hospital UniversitiSains Malaysia (HUSM) based on the aqli and naqli. It lacks of security in term of data integrity of the system. It will be enhanced in its security features which will be implemented with the data integrity feature and also password encryption to overcome the problems. As a result, an automated calculation of blood series and graph production as for data analysis will be implemented in this system.An approach of agile method is the chosen process to be used in realizing this research. This system will come out with the ability of protection in data integrity, password encryption and automatic calculation in order to reduce the fraud and human errors.